SMAC — A Modular Open Source Architecture for Medical Capsule Robots. (27th November 2014) - Marco, Beccani; Ekawahyu, Susilo; Christian Di, Natali; Pietro, Valdastri
The field of Medical Capsule Robots (MCRs) is gaining momentum in the robotics community, with applications spanning from abdominal surgery to gastrointestinal (GI) endoscopy. MCRs are miniature multifunctional devices usually constrained in both size and on-board power supply. The design process for MCRs is time consuming and resource intensive, as it involves the development of custom hardware and software components. In this work, we present the STORM Lab Modular Architecture for Capsules (SMAC), a modular open source architecture for MCRs aiming to provide the MCRs research community with a tool for shortening the design and development time for capsule robots. The SMAC platform consists of both hardware modules and firmware libraries that can be used for developing MCRs. In particular, the SMAC modules are miniature boards of uniform diameter (i.e., 9.8 mm) that are able to fulfill five different functions: signal coordination combined with wireless data transmission, sensing, actuation, powering and vision/illumination. They are small in size, low power, and have reconfigurable software libraries for the Hardware Abstraction Layer (HAL), which has been proven to work reliably for different types of MCRs. A design template for a generic SMAC application implementing a robust communication protocol is presented in this work, together with its finite state machine abstraction, capturing all the architectural components involved. The reliability of the wireless link is assessed for different levels of data transmission power and separation distances. The current consumption for each SMAC module is quantified and the timing of a SMAC radio message transmission is characterized. Finally, the applicability of SMAC in the field of MCRs is discussed by analysing examples from the literature.